Pulmonary Pathology in Perinatal and Neonatal Autopsies - Mohasin Jakirhusain Halgale; Sapna Shreyas Deshpande; Varad Manoj Agarwal (Annals of Pathology and Laboratory Medicine, 2026)
Background Neonatal mortality accounts for nearly half of under-five deaths globally, with pulmonary disorders being a leading cause. Clinical diagnoses are often limited, making autopsy essential for accurate cause-of-death determination and clinicopathological correlation. Methods This retrospective and prospective observational study was conducted at a tertiary care center from January 2020 to June 2025. A total of 102 perinatal and neonatal autopsies were analyzed (43 retrospective, 59 prospective). Clinical, maternal, and obstetric data were reviewed. Detailed autopsies with emphasis on pulmonary pathology were performed. Lung tissues were processed and examined histologically using hematoxylin and eosin staining, with special stains where required. Results Pulmonary pathology was the primary cause of death in 96.07% of cases and a contributing factor in 3.93%. Pneumonia was the most common lesion (56.87%), followed by respiratory distress syndrome (16.67%), meconium aspiration syndrome (13.72%), pulmonary hemorrhage (8.82%), pulmonary hypoplasia (1.96%), and congenital pulmonary airway malformation (1.96%). Pulmonary lesions accounted for 100% of deaths in full-term and post-term neonates and 88.89% in preterm neonates. Maternal complications were present in 36.27% of cases. Autopsy findings frequently revealed diagnoses not identified clinically. Conclusion Pulmonary disorders are the leading cause of perinatal and neonatal deaths. Autopsy remains indispensable for accurate diagnosis, identifying unsuspected conditions, and improving clinical care and public health strategies, particularly in resource-limited settings.